Soil Moisture Modulations of Dust Emissions Introduce Non‐Negligible Impacts on the Dust Direct Radiative Effect Across the Contiguous U.S. - Pedro A. Jiménez y Muñoz; Rajesh Kumar; Cenlin He; Jared A. Lee (Geophysical Research Letters)
Abstract Soil moisture increases the cohesive forces of soil particles, making it more difficult to lift the particles by the wind. As a result, the soil moisture modulates the airborne dust abundance, which in turn modulates the Earth's radiative balance. The importance of these soil moisture modulations on the radiative balance is unknown, however. Herein we use WRF‐Chem simulations to quantify the role of soil moisture modulations on the dust direct radiative effect. We focus on the contiguous U.S. due to the presence of important dust sources and good observational networks. Our results, based on the year of 2015, used a range of dust emissions and positive/negative soil moisture anomalies of ±25% and reveal a non‐negligible impact of around 15% in the net radiation at the top of the atmosphere and surface, with a smaller impact in the atmosphere.